Realizing New Data-Driven Business Models by Launching Containers into the Cloud - Zink, Mathias; Naumann, Victor; Harth, Andreas; Pflaum, Alexander (Digital Business Models in Industrial Ecosystems, 2021)
Data-driven business models are modern ways for innovation in traditional environments. The vision of the Internet of Things (IoT), by making products smart and leveraging the data into services, is a modern paradigm of value creation. A representative case study evolved business models for industrial containers in the automotive industry into a cloud-based data-driven business model. This publication outlines the background for industrial containers and provides insights into the relevant technological architectures. Additionally, the data-driven business model and the expansion of the ecosystem are outlined. Thereby this publication enhances the necessary interdisciplinary understanding of business model research and information science.<br